2013
DOI: 10.1038/pj.2012.226
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of conversion profiles inside a thick dental material photopolymerized in the presence of nanofillers

Abstract: In dental composites, the presence of inorganic fillers in the organic matrix leads to a light-scattering phenomenon that modifies the light intensity and, consequently, the ultimate polymerization yield. In this study, we aimed to characterize the impact of light scattering on the photopolymerization profiles inside thick materials. First, the photopolymerization kinetics of dental composites containing alumina or zirconia nanofillers were studied. An optimal formulation based on 75 wt% Bis-GMA, 25 wt% trieth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
(39 reference statements)
0
13
0
1
Order By: Relevance
“…Light attenuation within the material due to absorption by monomers and photoinitiators, scattering by filler particles and refraction at the filler/monomer interface is the cause of this limitation. As preponderant phenomenon, the light scattering jeopardizes light transmission and consequently, affects the conversion and depth of cure . Experimental results have demonstrated that the scattering coefficient decreases and the transmission efficiency improves when the refractive index difference between resin and filler narrows .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Light attenuation within the material due to absorption by monomers and photoinitiators, scattering by filler particles and refraction at the filler/monomer interface is the cause of this limitation. As preponderant phenomenon, the light scattering jeopardizes light transmission and consequently, affects the conversion and depth of cure . Experimental results have demonstrated that the scattering coefficient decreases and the transmission efficiency improves when the refractive index difference between resin and filler narrows .…”
Section: Introductionmentioning
confidence: 99%
“…As preponderant phenomenon, the light scattering jeopardizes light transmission and consequently, affects the conversion and depth of cure. [1][2][3] Experimental results have demonstrated that the scattering coeffi cient decreases and the transmission exhibit low reaction kinetics. [ 5,[12][13][14] In the case of fast photoinitiated polymerizations, the refractive index measurement by Abbe technique can usually be carried out only on fi nal photocured samples.…”
Section: Introductionmentioning
confidence: 99%
“…At one end of the spectrum are accurate physicochemical models accounting for each of the reaction steps (minimally photoinitiation, propagation, and termination) [19][20][21][22], nonuniform distributions of polymer chain length [23,24], generation and diffusion of thermal energy [15], mass transport [25], and intricate optical effects [26,27]. Such models, however, often suffer from an excessive number of parameters, some of which cannot be measured experimentally, and thus they offer limited insight and practical use.…”
Section: Introductionmentioning
confidence: 99%
“…Recent formulations [22,23] also enable predicting interface effects. The four-flux model can be used for various scattering systems as illustrated by recent publications [24][25][26][27]. However, even if the fourflux approach is much easier to use than more elaborated models, the simplicity of the two-flux approximation is still often preferred.…”
Section: Introductionmentioning
confidence: 99%